2008
DOI: 10.1128/aem.02188-07
|View full text |Cite
|
Sign up to set email alerts
|

Root Exudates Regulate Soil Fungal Community Composition and Diversity

Abstract: Plants are in constant contact with a community of soil biota that contains fungi ranging from pathogenic to symbiotic. A few studies have demonstrated a critical role of chemical communication in establishing highly specialized relationships, but the general role for root exudates in structuring the soil fungal community is poorly described. This study demonstrates that two model plant species (Arabidopsis thaliana and Medicago truncatula) are able to maintain resident soil fungal populations but unable to ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
371
1
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 675 publications
(394 citation statements)
references
References 36 publications
17
371
1
5
Order By: Relevance
“…The soil is described in detail in Broeckling et al (2008); soil from the same site was used in previous studies (Broeckling et al, 2008;Badri et al, , 2013a. Arabidopsis thaliana seeds were surface-sterilized with Clorox for one minute and subsequently rinsed four times with sterile distilled water.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The soil is described in detail in Broeckling et al (2008); soil from the same site was used in previous studies (Broeckling et al, 2008;Badri et al, , 2013a. Arabidopsis thaliana seeds were surface-sterilized with Clorox for one minute and subsequently rinsed four times with sterile distilled water.…”
Section: Methodsmentioning
confidence: 99%
“…Evidence demonstrating the close ties root exudates have on the microbial composition of the rhizosphere is mounting (Broeckling et al, 2008;Badri et al, , 2013aMicallef et al, 2009b;Chaparro et al, 2012Chaparro et al, , 2013, whereby many chemicals present in root exudates act as substrates, chemotactic or signaling molecules to orchestrate changes in microbial composition (Shaw, 1991;de Weert et al, 2002;Jain and Nainawatee, 2002;Horiuchi et al, 2005;Bais et al, 2006;Badri and Vivanco, 2009;Neal et al, 2012;Badri et al, 2013a). Recently, it was reported that the composition of Arabidopsis root exudates change following a plant developmental gradient (Chaparro et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Microbial diversity in the rhizosphere is linked to plant species mainly because interactions between root exudates and soil micro-organisms are highly dynamic in nature and based on coevolutionary pressures (Broeckling et al, 2008). In the past few years, only a few studies have focused on the impact of biocontrol agents (Cordier & Alabouvette, 2009;Vallance et al, 2011) on the structure and function of the rhizosphere microbiome.…”
Section: Rhizosphere Competence and Interactions With The Indigenousmentioning
confidence: 99%
“…Some bacterial endophytes associated with switchgrass and have been shown to increase plant growth (Xia et al, 2013). Plant root exudation patterns can select different microbial communities even between plant cultivars, resulting in strikingly different microbial communities in lab settings (Broeckling et al, 2008;Gschwendtner et al, 2010). To our knowledge, this is the first field demonstration of plant-specific microbial interactions between switchgrass ecotypes.…”
Section: Rhizodeposit Uptake Differed Between Ecotypesmentioning
confidence: 89%